536Patterns of change in lifestyle behaviours following childbirth. (2nd September 2021) - Makama, Maureen; Lim, Siew; Hill, Briony; Skouteris, Helen; Teede, Helena; Boyle, Jacqueline; Hodge, Allison; Earnest, Arul; Moran, Lisa
Abstract: Background: Lifestyle behaviours may worsen following childbirth due to barriers such as time constraints and reduced prioritization of personal health. We therefore aimed to assess the patterns of change in weight and lifestyle behaviours following childbirth in a longitudinal community-based cohort. Methods: Data from surveys 3 and 5 (ages 25-30 and 31-36 years) of the 1973-8 birth cohort of the Australian Longitudinal Study on Women's Health were used. We assessed changes in weight, energy intake, diet (diet quality, macronutrients and micronutrients), physical activity and sitting time in parous women compared to those who remained nulliparous by survey 5 using one-way analysis of covariance. Results: Of 4927 nulliparous women at survey 3, 2503 became parous by survey 5. Over 6 years, parous women had an increase in weight (1 kg; 95%CI 0.50, 1.54), higher energy intake (833.3 kJ/day; 95%CI 706.07, 960.52), better diet quality (1.4 units; 95%CI 0.81, 2.08), lower physical activity (-370.5 METmin/day; 95%CI -427.07, -313.87) and less sitting time (-1.8 hours/day; 95%CI -1.93, -1.60) than nulliparous women on adjusted analyses. On stratification of parity, the improvement in diet quality was only present in primiparous women and sitting time decreased with higher parity. Conclusion: There is a worsening in weight and some lifestyle behaviours following childbirth in Australian women. While higher parity was associated with further decreases in sitting time, improvements in diet quality were not maintained. Key message: Women need support to maintain healthy lifestyle behaviours amidst the challenges of caring for children, particularly with increasing family size.